Evaluation of Mixotrophy-Associated Gene Expression in Two Species of Polar Marine Algae - McKie-Krisberg, Zaid M.; Sanders, Robert W.; Gast, Rebecca J. (Frontiers in Marine Science, 2018)
Mixotrophic flagellates can comprise significant proportions of plankton biomass in marine ecosystems. Despite the growing recognition of the importance of this ecological strategy, and the identification of major environmental factors controlling phagotrophic behavior (light and nutrients), the physiological and molecular mechanisms underlying mixotrophic behavior are still unclear. In this study, we performed RNA-Seq transcriptomic analysis for two mixotrophic prasinophytes, Micromonas polaris and Pyramimonas tychotreta, under dissolved nutrient regimes that altered their ingestion of bacteria prey. Though the strains examined were polar isolates, both belong to genera with widespread distribution. Our aim was to characterize the transcriptomes of these two non-model phytoflagellates, identify transcripts consistent with phagotrophic activity and assess their differential expression in response to nutrient stress. De novo assembly of the transcriptomes yielded large numbers of novel coding transcripts with no known match within public databases. A summary of the transcripts by Gene Ontology terms showed many expected expression patterns, including genes involved in photosynthetic pathways and enzymes implicated in nutrient uptake pathways. Searches of KEGG databases identified several genes associated with intra-cellular digestive pathways actively transcribed in both prasinophytes. Differential expression analysis showed a larger response in P. tychotreta, where 23,373 genes were up-regulated and 1,752 were down-regulated in the low nutrient treatment when phagotrophy was enhanced. In contrast, in M. polaris, low nutrient treatments resulted in up-regulation of 314 transcripts while down-regulating 371. With respect to phagotrophic-related expression, 37 genes were co-expressed in both P. tychotreta and M. polaris, and although the response was less pronounced in M. polaris, it is consistent with differences in observed ingestion behavior. This study presents the first genomic data for Pyramimonas tychotreta, and also contributes to the limited available data for Micromonas polaris. Furthermore, it provides insight into the presence of genes associated with phagocytosis within the Prasinophyceae and contributes to the understanding of potential target genes required for the construction of a complete model of gene regulation of phagocytic behavior in algae.